Media Consumption Habit Among Students of Federal Polytechnic Bauchi Nigeria - Abdullahi, Shehu Abdulkadir (ALSYSTECH Journal of Education Technology, 2025)
The aimed of the study is to examine the preferences and behaviors of young individual concerning media usage among the student of federal polytechnic Bauchi. I sought to determine the types of media content students were expose to, the time allocated to various media sources daily, and their overall perception of media. The study was informed by the inadequacy of literature on the topic in the developing countries; Nigeria inclusive. I employed a well structure questionnaire to collect comprehensive insight into the prevalent media consumption patterns among polytechnic student. one hundred (100) respondents were randomly selected from the school of general studies, school of environmental studies and school of business studies I recommended the implementation of an orientation program within the polytechnic to raise awareness about fostering healthy media consumption habits within the polytechnic student. Media consumption habit are dynamic and may change over time due to technological advancements, shifts in preference and access to new platforms and content. Online streaming services such as Facebook, twitter and Tiktok has more patronage followed by newspaper and radio with very low listeners